European paganism: the realities of cult from antiquity to the Middle Ages - Dowden, Ken (Routledge, 2000)
1. Approaching paganism -- 2. Dividing the landscape -- 3. Focus I : spring, lake, river -- 4. Focus II : stone and tree -- 5. Area I : land -- 6. Area II : growth -- 7. Technology : statues, shrines and temples -- 8. Christian paganism -- 9. Pagan rite -- 10. Pagan time -- 11. A few aspects of gods -- 12. Priests -- 13. Cradle to grave -- 14. Unity is the thing.